INFLECTIONAL ANALYSIS OF MORPHOLOGICAL PROCESS IN TEACHING MORPHOSYNTAX THROUGH ONLINE LEARNING - Efransyah Efransyah; Helsa Feby Kurnia; Nalistya Zoheska Ildafiar (PROJECT (Professional Journal of English Education), 2021)
Inflectional is the smallest part of morphosyntax but it becomes important because it is the basic knowledge that students have to comprehend in learning and producing correct sentence. To understand them, the students have to learn it through virtual learning in COVID-19 pandemic era which  has changed the way of teaching and learning process especially in Morphosyntax. This research aimed to explore the types and the students’ difficulties in understanding inflectional process of morphology. This research used descriptive qualitative method to describe and to analyze the data. To collect the data, the researchers used two kinds of instruments namely pre-test, post-test, and interview. The population in this research consist of two classes from English Education Study Program at the fifth semester at IKIP Siliwangi.The result showed that the student mostly found the types of inflectional process namely plural form, 3rd singular person, past tense, progressive, comparative and superlative correctly while participle both in present and past tense form are mostly found incorrectly for they are having the higher function which are having similarity as verb progressive and as adjective at the same time. To understand the difference of the both function, the students are demanded to recognize well the structure of both. Keywords:  Inflectional Process, Morphosyntax, Online Learning